2013
DOI: 10.1016/j.cbpa.2013.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of food-deprivation and refeeding on the regulation and sources of blood glucose appearance in European seabass (Dicentrarchus labrax L.)

Abstract: H 2 O Gluconeogenesis Glycogenolysis Glucose 6-phosphatase Glucokinase NMR Sources of blood glucose in European seabass (initial weight 218.0 ± 43.0 g; mean ± S.D., n = 18) were quantified by supplementing seawater with deuterated water (5%-2 H 2 O) for 72 h and analyzing blood glucose 2 H-enrichments by 2 H NMR. Three different nutritional states were studied: continuously fed, 21-day of fast and 21-day fast followed by 3 days of refeeding. Plasma glucose levels (mM) were 10.7 ± 6.3 (fed), 4.8 ± 1.2 (fasted),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 50 publications
(71 reference statements)
6
18
0
Order By: Relevance
“…These expression data, combined with the maintenance of gluconeogenic enzyme activity, suggest that the gluconeogenesis pathway remained active under NoCHO nutrition according to the need for endogenous glucose production to sustain maintenance of normoglycemia due to the dietary habits and physiology of carnivorous species (9,12,61,62,65). Furthermore, this is consistent with previous in vivo and in vitro studies showing that the gluconeogenesis flux is never turned off in fed carnivorous teleosts (38,60). Moreover, when trout were submitted to a refasting period we showed that mRNA levels for most of the genes (pck1, fbp1b1, fbp1b2, g6pca, and g6pcb1b) were maintained at the same levels as in fed trout.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These expression data, combined with the maintenance of gluconeogenic enzyme activity, suggest that the gluconeogenesis pathway remained active under NoCHO nutrition according to the need for endogenous glucose production to sustain maintenance of normoglycemia due to the dietary habits and physiology of carnivorous species (9,12,61,62,65). Furthermore, this is consistent with previous in vivo and in vitro studies showing that the gluconeogenesis flux is never turned off in fed carnivorous teleosts (38,60). Moreover, when trout were submitted to a refasting period we showed that mRNA levels for most of the genes (pck1, fbp1b1, fbp1b2, g6pca, and g6pcb1b) were maintained at the same levels as in fed trout.…”
Section: Discussionsupporting
confidence: 89%
“…reviewed by Polakof et al 2012 (44)]. Moreover, another adaptive carnivorous trait is a higher rate of hepatic gluconeogenesis (48,54,56,60,63) than omnivorous species, allowing them to sustain endogenous glucose demands, i.e., maintenance of normoglycemia and production of energy using gluconeogenic amino acids and fat rather than dietary carbohydrates (9,12,61,62,65). Probably as a result of no dietary carbohydrate requirements, gluconeogenesis in adult fish is also poorly, if ever, regulated by carbohydrates (19,23,29,(33)(34)(35)37).…”
mentioning
confidence: 99%
“…It has been applied so far to study glucose and glycogen synthesis in seabass (58,59), alanine metabolism in gilthead seabream (60), and muscle protein synthesis in catfish (Ictalurus punctatus) (18). In the present study, FA synthesis was affected by the type of starch (raw vs. gelatinized), as already demonstrated in rainbow trout force-fed with 13 C-labeled starch (53).…”
Section: H-enrichments In Hepatic Tg Of Seabass (D Labrax) Fed With supporting
confidence: 70%
“…Insulin is considered as the most important factor for mammals to regulate and maintain the glucose equilibrium (Viegas et al, ). In experiments on the glucose tolerance in the snapper sea bream (Furuichi & Yasuo, ), the plasma insulin level increases with the increase in dietary glucose.…”
Section: Discussionmentioning
confidence: 99%